The institutions of the market : organizations, social systems, and governance - Ebner, Alexander; Beck, Nikolaus (Oxford : Oxford University Press, 2008)
Where do markets come from and what drives their evolution? How do organizations cope with the competitive dynamism of markets? What is the role of governance mechanisms in the institutional coordination of markets? Leading social scientists consider these questions and examine the institutional foundations of economic change.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Institutional economics; Evolutionary economics; Economics -- Sociological aspects